DIFFERENCES IN ACUTE POSTOPERATIVE PAIN AFTER ACL RECONSTRUCTION IN ADOLESCENT PATIENTS: ALL SOFT-TISSUE QUADRICEPS VERSUS HAMSTRING AUTOGRAFT. Issue 4 (28th April 2020) - Levy, Brandon; Holland, Erica; Bompadre, Viviana; Schmale, Gregory A.; Saper, Michael
Background: Postoperative pain after anterior cruciate ligament (ACL) reconstruction is a subjective experience that contributes significantly to patient satisfaction and subjective outcomes. As such, it is important for surgeons to counsel their patients and set appropriate expectations following surgery. ACL reconstruction with hamstring (HS) tendon autograft remains the most popular graft choice in adolescent patients with open physes, yet recently, reconstruction using all soft-tissue quadriceps tendon autograft has gained in popularity. However, studies are lacking that evaluate acute postoperative pain after quadriceps autograft. Hypothesis/Purpose: To investigate differences in acute postoperative pain between adolescent patients undergoing ACL reconstruction with all soft-tissue quadriceps versus HS autograft. Methods: A retrospective review was performed of 65 patients that underwent primary ACL reconstruction using either quadriceps (n = 33) or HS (n = 32) autografts between October 2017 and April 2019. All patients received ultrasound-guided adductor canal catheters and single-shot sciatic nerve blocks preoperatively and followed a standard postoperative multi-modal pain management plan. Intraoperative and postoperative intravenous (IV) morphine equivalents (MEQ), post-anesthesia care unit (PACU) length of stay (LOS), and PACU pain scores (numeric rating scale, 0-10) were recorded. Pain scores and supplemental oxycodone use were recorded on postoperative days (POD) 1-3. Differences were compared between the two groups. Results: The mean age at the time of surgery was 15.2 ± 1.5 years. There were no statistically significant differences in age ( p = 0.62), sex ( p = 0.72), BMI ( p = 0.18), concomitant meniscus repairs ( p = 0.71), or surgical time ( p = 0.52) between the two groups. There were no statistically significant differences in intraoperative IV MEQs ( p = 0.44), PACU IV MEQ ( p = 0.43), or PACU LOS ( p = 0.47) between the two groups. Patients treated with quadriceps autograft has lower max PACU pain scores (3.2 ± 3.2 vs 4.1 ± 3.1; p = 0.27) and required less supplemental oxycodone doses on POD 1 (1.1 ± 1.2 vs 1.8 ± 1.6; p = 0.07) but the differences were not statistically significant. Max pain scores (at rest and with movement) on POD 1-3 and oxycodone use on both POD 2 and POD 3 were similar between groups. Conclusion: In the setting of a multi-modal pain management plan including regional anesthesia, adolescent patients undergoing ACL reconstruction with quadriceps tendon autograft and hamstring autograft have similar pain levels and opioid use in the acute postoperative period.